Myoblast-derived exosomes reduce anticancer drug-induced muscle toxicity via an autocrine pathway: Myoblast exosomes reduce chemo muscle toxicity - lee, woojin; Sohn, Euijin; Kim, Sang Bum (Cellular and Molecular Biology, 2024)
During cancer treatment, cachexia, characterized by muscle loss, often occurs, with one of the contributing factors being muscle toxicity caused by anticancer drugs. It affects approximately 80% of patients with cancer, particularly those with digestive organ malignancies. However, effective treatment for this condition remains elusive. Therefore, in this study, we aimed to investigate the therapeutic potential of exosomes in relieving cachexia. Specifically, we examined the exosomes derived from muscle stem cells, which are involved in muscle cell regeneration and their role in controlling anticancer drug-induced muscle toxicity. First, exosomes secreted from myoblasts under depletion conditions were characterized. Exosomes were isolated under serum starvation conditions, displaying an average size of 113 nm and containing typical exosome marker proteins. Furthermore, electron microscopy confirmed their exosomal nature. To confirm the paracrine function of myoblast-derived exosomes (MDEs), a significant increase in cell viability was observed upon their application to myoblasts. No changes were observed in the cell cycle during exosome treatment. However, it was confirmed that the quantity of viable cells increased under serum starvation conditions. This suggests that MDEs possess the function of enhancing myoblast survival and overall cell viability. Cachexia, a prevalent condition in patients with cancer, often manifests as muscle cell depletion induced by anticancer drugs. The potential of MDEs to inhibit cell death induced by anticancer drugs was investigated. The findings revealed that while high concentrations of oxaliplatin and doxorubicin, known to induce cachexia, did not restore cell viability, lower concentrations did. This study suggests that MDEs may have the potential to control cachexia, a common side effect of anticancer drugs, by reducing muscle cell damage induced by anticancer drugs.